Quality and reliability of YouTube videos as a source of information on pulmonary rehabilitation - Coşar Ertem, Aytül; Ertem, Uğur (The European Research Journal, 2023)
Objectives: We aimed to evaluate the quality and reliability of the most watched YouTube videos in pulmonary rehabilitation (PR) and to determine the criteria that may be important in the selection of high quality and reliable videos by patients and their relatives. Methods: We searched for the keywords “pulmonary exercise,” “pulmonary rehabilitation,” and “pulmonary physiotherapy” on December 12th, 2021. Modified DISCERN (mDISCERN) and Global Quality Score (GQS) were used to assess the quality and reliability of the videos. Results: Of the 150 videos screened and 76 (50.7%) videos were identified for inclusion. The median mDISCERN score was 2, indicating that most of the videos were of low quality. A statistically significant relationship was found between video reliability classification in terms of video duration, time since upload, number of subscribers, and number of likes (p < 0.05). In addition, in terms of video upload source, it was determined that most of the high reliability videos were uploaded by healthcare professionals and most of the low reliability videos were uploaded by independent users (p < 0.05). When the videos were compared according to the quality groups subcategory, significant differences were detected in video duration, number of subscribers, average number of views per day, upload sources and mDISCERN scores (p < 0.05). Conclusions: According to the current study results, most of the PR-related videos on YouTube were found to be of poor quality and low reliability. Sharing more videos on social platforms by healthcare professionals in the future may be effective in increasing video quality and reliability.